Comparative pharmacoeconomic effectiveness of interleukin-17 inhibitors for the treatment of ankylosing spondylitis - T. V. Dubinina; I. Z. Gaydukova; N. А. Sableva; K. V. Sapozhnikov; V. D. Sokolova; D. G. Tolkacheva (Научно-практическая ревматология, 2022)
Objective – to compare the clinical efficacy and cost-effectiveness of IL-17 inhibitors (SEC, IXE, NTK) in the treatment of adult patients with ankylosing spondylitis (AS) in the healthcare system of the Russian Federation.Material and methods. The study is a sub-analysis of a previously published systematic review and network meta-analysis of the comparative efficacy of biologics in adult patients with AS in the Russian Federation. NNT values were calculated for BASDAI 50 and ASAS 20/40 after 16 weeks of therapy for all studied drugs. CpR was estimated for each biologic after 16 weeks and one year of therapy. Additionally, we carried out an assessment of the financial burden of the most cost-effective strategies for the treatment of AS.Results. The use of NTK is characterized by an average of no more than three patients needed to treat to achieve one ASAS 20/40 or BASDAI 50 response, while on IXE and SEC – no more than 4–5 patients need to be treated, depending on the estimated effectiveness criterion. According to CpR estimate, NTK is the most cost-effective IL-17 inhibitor for the treatment of AS, both after 16 weeks and after one year of therapy.Conclusion. The obtained results make it possible to compare the effectiveness of IL-17 inhibitors from a clinical and economic points of view and can be used both in decision making process of treatment strategies for individual patients, and at the population level – when deciding on the reimbursement of drugs